1995
DOI: 10.1099/0022-1317-76-9-2343
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite genome organization of a natural type 2 vaccine/nonvaccine recombinant poliovirus

Abstract: Intertypic vaccine/vaccine recombinant polioviruses are frequently isolated from vaccine-associated paralytic poliomyelitis cases (VAPP). We identified a vaccine/ nonvaccine poliovirus recombinant as the causative agent of a lethal VAPP. Partial RNA sequencing revealed a tripartite recombinant structure of the viral genome. This consisted of a central capsid core of vaccine origin flanked by two units of nonvaccine origin. The first nonvaccine genomic unit spanned the whole 5' noncoding region, and the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
9

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 23 publications
2
54
0
9
Order By: Relevance
“…Strain P2-V/598/80 has been shown to be a type 2 V/W recombinant in which the only conserved vaccine-derived sequence is the capsid-coding region studied (10). Almost all of the 5ЈUTR, the nonstructural protein-coding region, and the 3ЈUTR have been replaced by wild sequences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strain P2-V/598/80 has been shown to be a type 2 V/W recombinant in which the only conserved vaccine-derived sequence is the capsid-coding region studied (10). Almost all of the 5ЈUTR, the nonstructural protein-coding region, and the 3ЈUTR have been replaced by wild sequences.…”
Section: Resultsmentioning
confidence: 99%
“…These segments were thought to be derived from modified Sabin strains, wild PV, or from NPEVs. One of these recombinants was found to be a double recombinant containing wild sequences throughout the genome except in the capsid-encoding region (10). In this study, we further analyzed the genetic characteristics of these modified OPV-derived strains and assessed the occurrence of such strains in cases of VAPP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serotypes 1, 2 and 3 of wild-type PVs have been reported to recombine with each other (Dahourou et al, 2002;Furione et al, 1993). Wild-type and OPV strains have been reported to recombine (Dahourou et al, 2002;Georgescu et al, 1995;Guillot et al, 2000;Liu et al, 2000Liu et al, , 2003Yang et al, 2003) and PVs have been shown to recombine with serotypes of HEV-C (Brown et al, 2003;Jiang et al, 2007;Rousset et al, 2003). Furthermore, vaccine-derived PV strains, defined as having more than 1 % nucleotide differences in the VP1 protein coding region (reviewed recently by Agol, 2006;Kew et al, 2004), have been reported to have an interserotypic recombinant genome (Blomqvist et al, , 2004Martin et al, 2002) as well as a recombinant genome with a non-structural region from an unknown HEV-C strain (Arita et al, 2005;Kew et al, 2002Kew et al, , 2004Rakoto-Andrianarivelo et al, 2008;Rousset et al, 2003;Shimizu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Έχει υποστηριχθεί, ότι στην πλειοψηφία των μελετημένων περιπτώσεων πολιοϊών, ο ανασυνδυασμός υφίσταται στο μη -δομικό γονιδίωμα και συνήθως στο τμήμα 2Α -2C. Σε κάποιες περιπτώσεις έχουν αναφερθεί γεγονότα ανασυνδυασμού μεταξύ της 5΄ NTR και της P1 κωδικής περιοχής (του καψιδίου) (Georgescu et al, 1995), ενώ ο ανασυνδυασμός εντός του γενωμικού τμήματος, που κωδικοποιεί για τις πρωτεΐνες του καψιδίου, φαίνεται να αποτελεί περισσότερο εξαίρεση παρά κανόνα των περιπτώσεων ανασυνδυασμού (Blomquist et al, 2003).…”
Section: α412 ο ανασυνδυασμός στους πολιοϊούςunclassified